ChemInform Abstract: A New Method for the Benzylic Oxidation of Alkylarenes Catalyzed by Hypervalent Iodine(III). Issue 22 (13th May 2013) - Xu, Yuan; Yang, Zhenping; Hu, Jiantao; Yan, Jie
Abstract The convenient protocol affords high yields for the cyclic ketones, whereas linear ketones are formed with moderate to low yield except in the case of acetophenone (VIa).